The highest elevation record of a large Indian civet Viverra zibetha and the record of Siberian weasel Mustela sibirica in Langtang National Park, Nepal - Basnet, Hari; Thapa, Bhumika; Tamang, Kanchha (Nepalese Journal of Zoology, 2024)
Large Indian civet Viverra zibetha is generally found below 2,500 m above sea level. However, our documentation of this species at Cholangpati, Langtang National Park at 3,622 m asl, marks the highest elevation ever documented for this species globally. Similarly, our sighting of the Siberian weasel Mustela sibirica in the Gosaikunda and Langtang Valley trekking route is the first recorded observation in the Langtang National Park. These discoveries contribute valuable insights into the distribution of these animals, emphasizing the significance of opportunistic sightings.